Social eating as a favor exchange facilitator: New survey evidence from China - Yanjie Bian; Lingfeng He (economic sociology. perspectives and conversations, 2022)
Social eating - or eating a meal with significant others - is universally important for social networking in society. This article reviews a research program on social eating as a network builder and resource mobilizer for favor exchanges, and presents new survey evidence on patterns of participation in social eating and favor exchanges in China today.
Keywords: 300